2002
DOI: 10.1046/j.1365-2214.2002.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Financial effects for families after the death of a disabled or chronically ill child: a neglected dimension of bereavement

Abstract: Findings provide further evidence of the financial impact for families of caring for severely disabled children. This study shows how this impact can extend far into the period after death. Findings indicate the need for financial advice and support to families both during the period of care and after bereavement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Parents (or caregivers) have to manage their time between caring responsibilities and everyday domestic tasks [24,25]. Disturbances to employment patterns may have important financial implications, in addition to any extra expenditure incurred [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Parents (or caregivers) have to manage their time between caring responsibilities and everyday domestic tasks [24,25]. Disturbances to employment patterns may have important financial implications, in addition to any extra expenditure incurred [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…From the time a child is suspected of having cancer, parents are often faced with disruptions in daily routines and family life, including changing caregiver or spousal roles, threats to employment and financial strain, and emotional challenges that significantly contribute to the cancer experience. These additional stressors in combination with caring for healthy family members and maintaining other relationships can be extremely difficult for couples.…”
Section: Introductionmentioning
confidence: 99%
“…Minority groups were disproportionately affected, as they typically experienced higher death rates and had lower incomes. Other studies investigated the financial impact of the death of a child (Corden, Sainsbury & Sloper, 2004;Corden, Sloper & Sainsbury, 2002) and the death of a partner (Corden & Hirst, 2013;Corden, Hirst & Nice, 2010;Fan & Zick, 2004). These studies found that preceding and following death there is often a period of increased expenditure and decreased income.…”
Section: Government Role In Indigent Funeralsmentioning
confidence: 99%